Determinants of knowledge, attitudes, and practices toward edible insect consumption in Rwanda’s Nyabihu and Ngororero districts - Niyonzima, Francois Niyongabo; Iradukunda, Patrick Gad; Iyamuremye, Aloys; Nsabayezu, Ezechiel; Cheseto, Xavier (Journal of Food Technology Research, 2026)
As global populations confront food insecurity and malnutrition, edible insects have emerged as a sustainable and nutrient-rich alternative. However, consumer acceptance remains a critical barrier to widespread adoption. This study investigates the socio-demographic and cultural factors influencing knowledge, attitudes, and practices (KAP) regarding edible insect-based foods in Nyabihu and Ngororero districts of Rwanda. A cross-sectional study was performed with 397 randomly selected households using a structured questionnaire. Data were analyzed using descriptive statistics, chi-square tests, and logistic regression to identify predictors of KAP levels. Key informant interviews provided qualitative insights into cultural perceptions and consumption trends. Among respondents, 72.5% demonstrated proficient knowledge of edible insects, 70.5% displayed favorable views, and 62.4% had consumed edible insects. Higher education, professional occupations (including civil servants and traders), and the perception of insects as a traditional food source were strongly correlated with enhanced knowledge and positive attitudes (p < 0.05). Conversely, cultural taboos were significant negative predictors, reducing both knowledge and attitudes. Students, traders, and government workers exhibited higher levels of positive behaviors, whereas inhabitants of Ngororero and those citing cultural taboos were less inclined to participate in entomophagy. Despite a promising knowledge and attitudinal baseline, actual consumption remains below optimal levels, constrained by persistent socio-cultural barriers. District leaders and policymakers can utilize these results to implement targeted nutrition campaigns aimed at eliminating cultural taboos and promoting edible insect consumption. Rwandan food technologists, academicians, and entrepreneurs can leverage these findings to develop insect-based food products to combat child malnutrition.